Porphyromonasgingivalis gingipains potentially affect MUC5AC gene expression and protein levels in respiratory epithelial cells. Issue 2 (30th December 2020) - Miya, Chihiro; Cueno, Marni E.; Suzuki, Ryuta; Maruoka, Shuichiro; Gon, Yasuhiro; Kaneko, Tadayoshi; Yonehara, Yoshiyuki; Imai, Kenichi
Abstract : Porphyromonas gingivalis (Pg) is a periodontopathic pathogen that may affect MUC5AC‐related mucus hypersecretion along airway epithelial cells. Here, we attempted to establish whether Pg virulence factors (lipopolysaccharide, FimA fimbriae, gingipains) affect MUC5AC in immortalized and primary bronchial cells. We report that MUC5AC gene expression and protein levels are affected by Pg culture supernatant, but not by lipopolysaccharide or FimA fimbriae. Cells treated with either Pg single (Kgp or Rgp) or double (Kgp/Rgp) mutants had altered levels of MUC5AC gene expression and protein levels, and MUC5AC staining of double mutant‐treated mouse lung cells showed that MUC5AC protein levels were unaffected. Taken together, we propose that Pg gingipains may be the primary virulence factor that influences both MUC5AC gene expression and protein levels. Abstract : MUC5AC gene expression and protein levels are affected by Pg culture supernatant, but not by lipopolysaccharide or FimA fimbriae. Cells treated with either Pg single (Kgp or Rgp) or double (Kgp/Rgp) mutants had altered levels of MUC5AC gene expression and protein levels, and MUC5AC staining of double mutant‐treated mouse lung cells showed that MUC5AC protein levels were unaffected.